Public Progress, Data Management and the Land Grant Mission: A Survey of Agriculture Researchers' Practices and Attitudes at Two Land-Grant Institutions. - Peter Fernandez; Christopher Eaker; Miriam L. E. Steiner Davis (Issues in Science and Technology Librarianship, 2016)
This article reports results from a survey about data management practices and attitudes sent to agriculture researchers and extension personnel at the University of Tennessee Institute of Agriculture (UTIA) and the College of Agricultural Sciences and Warner College of Natural Resources at Colorado State University. Results confirm agriculture researchers, like many other scientists, continue to exhibit data management practices that fall short of generally accepted best practices. In addition, librarians, and others seeking to influence future behavior, may be informed by our finding of a relationship between the land-grant mission and researchers' data management practices. [ABSTRACT FROM AUTHOR]